ANALISIS KELAYAKAN USAHA SAPI POTONG DALAM BERBAGAI TINGKAT KEPEMILIKAN DI DESA TULABOLO BARAT - Nurinda Abas; Mahludin Baruwadi; St Aisyah Ramli (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2023)
One of the people's choices in West Tulabolo Village is to create new jobs by running a beef cattle business to support the village economy. The objectives of this research are (1) to understand the process of cultivating beef cattle, (2) to analyze costs, income, and revenues, and (3) to analyze the feasibility of beef cattle farming in various levels of ownership in West Tulabolo Village. This research used a sample of 27 beef cattle breeders using a saturated sampling technique. This research uses primary data sources and secondary data. Apart from that, the types of data used include qualitative and quantitative data. Data collection methods use surveys, interviews, and literature studies. The research results show that (1) the process of cultivating beef cattle starts from preparation, breeding, maintenance and enlargement, fattening (2) the income received from a scale of 1-2 heads to more than 5 heads is IDR 17.929.425 to IDR 63.137.959 and (3) the beef cattle farming business in West Tulabolo Village is said to be feasible based on the results of the R/C and B/C analysis which shows >1.